Antibacterial Activity of Undoped and Cu2+ Doped Tin Oxide Nanoparticles Synthesized by Microwave Irradiated Solvothermal Method - Abhirama, K.J.; Saraswathi, N.; Madhu, K.U. (Asian Journal of Chemistry, 2022)
In present work, a simple and facile microwave irradiated solvothermal method was applied for the synthesis of undoped and Cu2+ doped tin oxide nanoparticles. Thermal characterization was performed to study the thermal stability and to fix the annealing temperature. All the prepared samples were annealed at 500 ºC and then characterized. Structural, morphological and optical characterizations were done using PXRD, TEM, SEM and UV-Vis NIR analysis. The PXRD measurement shows the tetragonal phase of tin oxide. Agglomerated and spherical morphology was observed in SEM and TEM micrographs. Presence of blue shift was observed in the absorption spectra of the prepared samples. Elemental compositions of the samples were analyzed using EDX patterns. Magnetic characterization was performed using vibrating sample magnetometer and the analysis revealed that the prepared samples were diamagnetic in nature. Antibacterial studies showed the efficient activity against the Gram-positive and Gram-negative bacterial stains.